KUALITAS DIET, STATUS GIZI DAN STATUS ANEMIA WANITA PRAKONSEPSI ANTARA DESA DAN KOTA - Cindy Fariski; Fillah Fithra Dieny; Hartanti Sandi Wijayanti (PERSATUAN AHLI GIZI INDONESIA, 2020)
The health status during the preconception period was important to prepare pregnancy. Living patterns that can affect diet quality and nutritional status. This study aimed to analyze the differences in diet quality, nutritional status, and anemia between preconception women in rural and urban areas. This study was conducted using a cross-sectional design that consisted of 68 brides aged 16-35 years selected by consecutive sampling. Diet quality was obtained by diet quality index international (DQI-I) form. Nutritional status based on body mass index (BMI) and mid-upper arm circumference (MUAC). Hemoglobin levels were measured by the cyanmethemoglobin method. Data were analyzed by Independent T-test and Mann Whitney. Subjects in rural and urban areas had low diet quality. The score of variation in the type of protein intake, total fat, and saturated fat was higher in rural areas than urban areas (p=0,001; p=0,013; p=0,002). The mean BMI and MUAC were higher in urban subjects than rural subjects but the hemoglobin levels of rural subjects were higher than urban subjects. The subjects of anemia in urban was 23,5 percent were higher than rural was 14,7 percent but the risk of chronic energy deficiency in rural was 55,9% were higher than urban was 11,8 percent. There were no differences in diet quality and hemoglobin levels between preconception women in rural and urban areas (p=0,990; p=0,116). There were a differences in BMI and MUAC (p=0,026; p=0,001). There were differences in nutritional status based on BMI and MUAC in both areas. There were no differences in diet quality and hemoglobin levels in rural and urban areas